2003
DOI: 10.1259/bjr/21553230
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fluoroscopy time and dose–area product values duringad hocone-vessel percutaneous coronary angioplasty

Abstract: X-ray exposure during radiologically guided interventional procedures may have some deleterious effects. The aim of our study was to analyse the factors affecting patient dose during percutaneous coronary angioplasty (PTCA). We evaluated radiation dose during coronary angiography followed by one-vessel PTCA in 402 consecutive patients who were treated by three experienced physicians using both femoral and radial techniques. Fluoroscopy time (t) and patient dose measured by a dose-area product (DAP) meter were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 19 publications
3
30
2
Order By: Relevance
“…Vascular complications were more frequent for femoral access at 5.9% compared to 2.1% for radial access. Larrazet et al [18] report a higher DAP with radial access, median 175 Gy cm 2 compared to 138 for femoral access. Their study was not randomised and resulted in DAP values considerably higher than in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Vascular complications were more frequent for femoral access at 5.9% compared to 2.1% for radial access. Larrazet et al [18] report a higher DAP with radial access, median 175 Gy cm 2 compared to 138 for femoral access. Their study was not randomised and resulted in DAP values considerably higher than in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Because some variables such as body mass index, the treatment of complex lesions, and the different angulation of the X-ray tube may have biased the radiation dose, [11][12][13] we also tested our hypothesis in 6 cases of simultaneous left and right radial cannulation during fluoroscopy in the anteroposterior position of the X-ray tube. In these cases, a snapshot evaluation of the radiation dose to the operator's left arm Radiation dose at the wrist was significantly higher compared with the rest of the body, but this difference was significant only in the right radial approach group.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have been raised about prolonged procedure time and increased radiation exposure to the operators by using radial route of access (4)(5)(6). Although, some studies have shown that with increasing operator experience radiation exposure can be minimized with transradial approach (TRA) and hence majority of radial operators assume that special radiation exposure precautions are unnecessary (7,8).…”
Section: Introductionmentioning
confidence: 99%